2013
DOI: 10.1017/s1366728913000102
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing of the target language during source language comprehension in interpreting

Abstract: Two experiments were conducted to test the hypothesis that the parallel processing of the target language (TL) during source language (SL) comprehension in interpreting may be influenced by two factors: (i) link strength from SL to TL, and (ii) the interpreter's cognitive resources supplement to TL processing during SL comprehension. The influence of the first factor was supported by the contrasting performance on bidirectional SL and TL interpreting tasks by unbalanced bilingual student interpreters, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Different lexicons are activated to different degrees to ensure successful rendition (i.e., source language comprehension and target language production, monitoring of ones' own speech, and no interference from source language during target language production). 718 Yanping Dong and Ping Li translation equivalent, which needs little attention and saves resources (Dong & Lin, 2013). But in most cases, the translation of messages requires efforts.…”
Section: Structural Account Of Language Control: Language-modality Comentioning
confidence: 99%
See 1 more Smart Citation
“…Different lexicons are activated to different degrees to ensure successful rendition (i.e., source language comprehension and target language production, monitoring of ones' own speech, and no interference from source language during target language production). 718 Yanping Dong and Ping Li translation equivalent, which needs little attention and saves resources (Dong & Lin, 2013). But in most cases, the translation of messages requires efforts.…”
Section: Structural Account Of Language Control: Language-modality Comentioning
confidence: 99%
“…During the input phase, apart from the main subtask of comprehending the incoming information, the interpreter generally has to take notes at the same time; during the output phase, apart from the main subtask of producing the TL, the interpreter generally has to consult notes to reconstruct the messages. Compared with simply listening to a segment of speech and taking notes without having to recall it later in another language, the input phase in consecutive interpreting is more multi-tasking because while listening to the input speech, the interpreter is already searching for translation equivalents in the mind (e.g., Dong & Lin, 2013), and notes may be taken in either the input or the output language. What is more, the interpreter is required to be as accurate as possible in the transmission of messages, which puts more demands on the input phase when messages have to be registered either in the mind or in the notes.…”
Section: Processing Control: Divided Attention and Language Processinmentioning
confidence: 99%
“…1. The participants of the present study were exactly the same group of participants as in Dong and Lin (2013) that studied their parallel processing of the target language (TL) during SL comprehension. And the English-to-Chinese CI task was the same as used in Cai et al (2015).…”
Section: Notesmentioning
confidence: 99%
“…We thus hypothesized that the updating function of WM was closely related to CI performance, and CI training could help enhance updating . In addition, interpreters may process the source language input in a parallel way, i.e., their processing of the source language may be influenced by the target language (e.g., Dong and Lin, 2013 ), suggesting that interpreters may have a more efficient way processing the source language so that they can recall details better and perform better in tasks of verbal WM spans. Furthermore, Ecker et al (2010) found that WM capacity was a strong predictor of WM updating, suggesting that WM spans and WM updating are closely related.…”
Section: Introductionmentioning
confidence: 99%